Emotion recognition in progressive supranuclear palsy. Issue 10 (17th September 2009) - Ghosh, B C P; Rowe, J B; Calder, A J; Hodges, J R; Bak, T H
Abstract : Progressive supranuclear palsy (PSP) is an atypical parkinsonian syndrome characterised by akinesis, rigidity, falls, supranuclear gaze palsy and cognitive, particularly executive, dysfunction. This study examined the extent to which emotion recognition is affected by PSP. Although deficits in the recognition of emotion have been reported in several diseases which share clinicopathological characteristics with PSP, it has never been studied systematically in PSP. Twenty-four patients with probable or definite PSP and matched healthy controls were studied using tests of facial identity and facial emotion recognition. Patients were not impaired in recognising famous faces, but they showed significant deficits in the recognition of emotions, particularly negative emotions. Moreover, emotion recognition was strongly correlated with the severity of other cognitive deficits in PSP, but not disease duration. Deficits in emotion recognition form an integral part of the cognitive spectrum of the disease. The findings point to the pathological involvement of key regions necessary for the processing of emotions and to a subtype of PSP with cognitive and emotion recognition impairments. The acknowledgement of deficits in emotion recognition is important for management of both patients and their carers.